Manajemen Penguatan Pendidikan Karakter Berkebinekaan Global dan Gotong-Royong di SMP Negeri 39 Semarang - Wahyuningsih, Putri; Muhdi, Muhdi; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Putri Wahyuningsih. 2023, "Management of Strengthening Global Diversity and Mutual Cooperation at SMP Negeri 39 Semarang." Advisor's Thesis 1) Dr. Muhdi, S.H., M.Hum, 2) Dr. Noor Miyono, M.Sc. Character education is a continuous and never-ending process, resulting in continuous quality improvement aimed at realizing the human figure of the future. Character education emphasizes example, creating an environment, and habituation through various scientific tasks and conducive activities. The aim of this research is to find out how management strengthens character education at SMP Negeri 39 Semarang. Strengthening character education with global diversity and mutual cooperation at SMP Negeri 39 Semarang is closely related to school management. Management of strengthening student character education includes: (1) Planning stage for strengthening character education; (2) Organizing stage of strengthening character education; (3) Implementation stage of strengthening character education; (4) and Supervision stage of strengthening character education. This research uses a qualitative approach. Data collection techniques use observation, interviews and documentation. The data collected from this technique is analyzed using data reduction, data presentation, and verification (conclusion). Based on the results of the research and discussion, it can be concluded that strengthening character education at SMP Negeri 39 is carried out in four main activities, namely: learning activities, Pancasila Student Profile Strengthening Project (P5) activities, extracurricular activities, habituation activities. Keywords: Management, Character Education, Global Diversity, Mutual Cooperation